Molecular Viability Assay: Improving Leprosy Diagnosis beyond Current Gold Standard - Clara Imaniar; Ibnu Agus Ariyanto; Yeva Rosana (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Neglected tropical diseases are still part of the health problems faced by the world. One of the neglected tropical diseases that has not yet reached 100% elimination is leprosy. Mycobacterium leprae is the pathogen responsible for leprosy, a chronic infectious disease that affects the skin and peripheral nerves and can lead to significant disability if left untreated. Currently, the gold standard for diagnosis is detecting acid-fast bacilli (AFB) with Ziehl-Neelsen staining; however, this method cannot distinguish between living and dead bacteria, complicating treatment assessment, relapse detection, and resistance tracking. Therefore, more accurate diagnostic instruments that can differentiate bacterial viability are needed. Since M.leprae cannot be cultured in artificial media, molecular-based assays are promising tools for rapid diagnosis. This study aims to identify recent assays for assessing bacterial viability in leprosy. Articles used are limited to the publication year between 2019 until 2024 from databases such as PubMed, ProQuest, Scopus and Google Scholar, using PRISMA methods. After filtration, from 143 articles we found 5 articles that discussed the viability of leprosy-causing bacteria. The selected studies showed that molecular assays to determine bacterial viability can be used and explored to strengthen the existing gold standard for monitoring treatment of leprosy patients